THE ROLE OF DIALOGIC COMMUNICATION IN TEACHING ENGLISH METHODOLOGY - Yusupaliyeva Fazilat (American Journals, 2024)
Teaching foreign languages is considered essential for part of education. In this paper the information is given about importance of dialogical conversation to develop elementary school pupils’ speaking skill.
Keywords: Communications, school, pupil, knowledge, students.